Avaliação da diversidade genética e do manejo reprodutivo em pacu, Piaractus mesopotamicus - Povh, Jayme Aparecido (2007)
: In many Brazilian Rivers it has been observed a decrease and even a disappearance of many fish species caused by factors as pollution, building dams and over fishing. Among these species, the pacu (Piaractus mesopotamicus) nowadays is barely found in some rivers, for example, in the Paranapanema River. As a fonn to outline the impacts on fish's populations, the restocking technique has been very used in Brazil. However, this practice has been realized, in general, without any scientific support. Facing this scenery, any action that seeks the environment recovery should look for the monitoring by scientific ways not basing in suppositions. Among methodologies for this aim, the molecular markers are tools that can be used to recognition and genetic characterization of stocks (native and broodstocks) and fish that will be get free in the environment. So, the works presented here evaluated the genetic diversity of Piaractus mesopotamicus collected in the middle of Paranapanema River, of fish farming broodstocks with restocking purpose, and also offspring's obtained by extrusion and semi-natural reproductive systems. For these evaluations the molecular markers RAPD (Random Amplified Polymorphic DNA) and microsatellite were using, both based on PCR (Polymerase Chain Reaction). The results showed a lower genetic variability of stock in relation to population, promoted by founder effect of this stock and/or due to different origin of fish that formed the stock. However, the moderate genetic differentiation and high Nm obtained indicate that populations and stock presented a similar genetic pool. As for the reproductive systems, a great genetic variability reduction was observed in the offspring from extrusion reproduction system in relation to the semi-natural system. Although this last system has presented dominance of some reproducers, due multiple patemities existence, there was a genetic Variability maintenance of offspring in relation to reproducers.